2017
DOI: 10.1073/pnas.1615949114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of multispecific recognition of Calmodulin through conformational changes

Abstract: Calmodulin (CaM) is found to have the capability to bind multiple targets. Investigations on the association mechanism of CaM to its targets are crucial for understanding protein-protein binding and recognition. Here, we developed a structure-based model to explore the binding process between CaM and skMLCK binding peptide. We found the cooperation between nonnative electrostatic interaction and nonnative hydrophobic interaction plays an important role in nonspecific recognition between CaM and its target. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 67 publications
(112 reference statements)
1
50
0
Order By: Relevance
“…The ability of individual N- and C-terminal lobes of CaM to independently associate to either distinct sites on the same protein or to the same site on two distinct polypeptides, thus facilitating their dimerization, have been described for numerous CaM targets, although in many instances, the affinity of individual lobes with their target sequence is lower than that with the AC H-helix. Our data further highlight the remarkable conformational diversity of CaM upon binding to its targets [ 44 49 ].…”
Section: Discussionmentioning
confidence: 55%
“…The ability of individual N- and C-terminal lobes of CaM to independently associate to either distinct sites on the same protein or to the same site on two distinct polypeptides, thus facilitating their dimerization, have been described for numerous CaM targets, although in many instances, the affinity of individual lobes with their target sequence is lower than that with the AC H-helix. Our data further highlight the remarkable conformational diversity of CaM upon binding to its targets [ 44 49 ].…”
Section: Discussionmentioning
confidence: 55%
“…CaM is an important calcium sensor studied extensively due to its flexibility and structural plasticity toward numerous substrates (29,30). Structural and computational studies have explored the interactions between CaM and a diverse heterogeneous group of interacting proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These conformational changes expose nonpolar surfaces of CaM, which then bind to nonpolar regions on the target proteins. Target proteins have CaM-binding sites that may vary in their amino acid sequences but share common features of having bulky hydrophobic residues separated by a specific number of residues and a helix-forming propensity (28)(29)(30). Furthermore, a recent report elucidates how CaM regulates the interaction of the ER Ca 2+ sensor, the stromal interaction molecule (STIM), with the plasma membrane pore-forming subunit, Orai1 (31).…”
mentioning
confidence: 99%
“…We have previously shown that the P454 peptide, residues 454-484 from the CyaA translocation region, exhibits membrane-active properties similar to antimicrobial peptides (AMPs) 67 . As with certain AMPs, the P454 peptide displays biophysical properties that are similar to that of many calmodulin-binding peptides: they can form amphiphilic helices, they are positively charged and contain a few aromatic or hydrophobic residues involved in complex stabilization [68][69][70] . Indeed, we found that P454 binds calmodulin (CaM) in solution in a calcium-dependent manner as shown by analytical ultracentrifugation and far-UV circular dichroism spectroscopy ( Figure S2 and Table S1).…”
Section: -The P454 Peptide From the Cyaa Toxin Binds To Calmodulinmentioning
confidence: 99%